First Report of Southern Blight on Aloe vera Caused by Athelia rolfsii in China - Zhu, Jun Zi (Plant disease, 2022)
Aloe vera (L.) Burm f., which belongs to the family Aloaceae, is a perennial succulent plant and cultivated for its medicinal, cosmetic, vegetable and ornamental uses. In summer of 2021, about 15% (60 infected among 400 surveyed plants) of A. vera (A. barbadensis) plants in two gardens in Lishui, Zhejiang Province of China showed symptoms of southern blight disease. Symptomatic plants primarily exhibited slightly sunken water-soaked, dark brown lesions on taproot and basal part of the stems. As the disease progressed, leaves in the basal part of stems and subsequently the whole plant rotted and withered, with white mycelial mats occurring on infected stems and leaves. Numerous brown, spherical sclerotia were observed on the colonized tissues and soil surfaces around the infected plants. Mycelial fragments and sclerotia from symptomatic leaves were plated directly to potato dextrose agar (PDA) amended with 100 μg/ml streptomycin and incubated at 26°C in the dark. By hyphal-tip method, a total of five pure isolates were obtained from five diseased leaf samples. When cultured on PDA at 26°C for three days, colonies showed white and thick aerial mycelium, with a radial growth rate of 23.7 mm/day. Typical clamp connection structures were observed microscopically after three days and numerous globoid, rapeseed shape sclerotia, measuring 1 to 2 mm in diameter (n=50) formed after six days. These sclerotia were initially white and gradually turned dark brown with age. On the basis of morphological characteristics, the fungal isolates were identified as Athelia rolfsii (Curzi) C.C. Tu & Kimbr (anamorph Sclerotium rolfsii Sacc) (Mordue 1974). The internal transcribed spacer (ITS) and translation elongation factor 1-α gene (TEF1) regions of a representative isolate LHBJ2-4 were amplified and sequenced using the primers ITS4/ITS5 (White et al. 1990) and EF1/EF2, respectively (accession no. MZ956758 and OL365370). BLASTn search showed that the amplified ITS and TEF1 sequences had 99.71% (680/682 bp) and 99.80% (498/499 bp) identity with the A. rolfsii isolates CBS 115.22 (MH854711.1) and Sr_286 (JF267815), respectively. Neighbor-joining phylogenetic tree based on the ITS sequences revealed that LHBJ2-4 clustered with A. rolfsii isolates. For pathogenicity test, three potted A. vera plants (~30 cm tall) were inoculated by placing a 0.5 cm mycelial plug of isolate LHBJ2-4 (three-day old) at the base of each A. vera plant. Three A. vera plants inoculated with sterile PDA plugs served as controls. All the inoculated plants were placed in a growth chamber at 27°C under a 12/12 h light/dark cycle. The inoculation assays were carried out twice. After 5 to 7 days, stem bases of the inoculated plants showed brown lesions that were similar to those observed in the field. However, control plants remained symptomless. Athelia rolfsii was re-isolated from all the inoculated plants and identified using morphological and molecular method described above, thus confirming Koch's postulates. Although A. rolfsii has been reported to cause disease on A. vera in India (Dubey and Pandey 2009), to the best of our knowledge, this is the first report of A. rolfsii causing southern blight on A. vera in China. Because A. rolfsii has a wide host range and is difficult to control (Punja 1985), occurrence of southern blight in China might be a serious threat for A. vera production and appropriate management strategies should be developed to control this disease